OPTIMIZATION OF WATER UTILIZATION FOR ELECTRIC ENERGY AT TIRO RESERVOIR, PIDIE DISTRICT - Azmeri Azmeri; Maimun Saputra (JURNAL TEKNIK SIPIL, 2012)
Abstract: This study aims to find The Tiro Reservoir operation pattern using non-linear optimization technique to obtain the optimal total electrical energy. Method of operation of the reservoir system optimization is accomplished using the Solver in Microsoft Excel. Calculation of discharge was calculated for the probability of occurrence of 20% (wet period), 50% (normal period) and 80% (dry period). As for the water needs taken into account for purposes of irrigation, water supply, and maintenance needs. Projected water needs of irrigation districts Tiro done in 4 phases, namely in 2011, 2016, 2026 and 2036. The results obtained from the optimization process Tiro Reservoir operation using non-linear program is the amount of water released each month and the total amount of annual energy. The amount of release based on the type of wet, normal and dry. Release and optimum total annual energy that can be produced, performed for the year 2011, short-term (2016), medium term (2026) and long-term (2036). Based on the type of normal period, the total releases for the year 2023 amounting to 88.214 x 106 m3, while the total electrical energy generated at 122.8 GWH.Keywords : Optimization, Solver, water availability, water requirements, non-linear, releases, energyAbstrak: Penelitian ini bertujuan untuk mendapatkan pola pengoperasian Waduk Tiro dengan menggunakan teknik optimasi non linier sehingga diperoleh total energi listrik yang optimal. Metode optimasi sistem pengoperasian waduk dilakukan dengan menggunakan program Solver pada Microsoft Excel. Perhitungan debit dihitung untuk probabilitas kejadian 20% (debit tahun basah), 50% (debit tahun normal) serta 80% (debit tahun kering). Sedangkan untuk kebutuhan air diperhitungkan untuk keperluan irigasi, air bersih, dan kebutuhan maintenance sebagai tetap menjaga ekosistem sungai. Proyeksi kebutuhan air irigasi kecamatan Tiro dilakukan dalam 4 tahap yaitu tahun 2011, tahun 2016, tahun 2026 dan tahun 2036. Hasil yang diperoleh dari proses optimasi pengoperasian Waduk Tiro dengan menggunakan program non linier adalah besarnya release air tiap bulan serta besarnya total energi tahunan. Besarnya release air berdasarkan jenis tahun basah, normal dan kering. Release air dan total energi tahunan optimum yang dapat dihasilkan, dilakukan untuk tahun 2011, jangka pendek (2016), jangka menengah (2026) dan jangka panjang (2036). Berdasarkan jenis tahun normal, total release untuk tahun tahun 2023 sebesar 88,214 x 106 m3, sedangkan total energi listrik yang dihasilkan sebesar 122,8GWH.Kata kunci : Optimasi, Solver, ketersedian air, kebutuhan air, non linier, release, energi